The Digital Frontier : Infrastructures of Control on the Global Web - Sangeet Kumar (Book collections on Project MUSE., 2021)
In analyzing the nature of power and control on the web, The Digital Frontier is a great read for readers, scholars, activists and students inspired by the utopian dream of a truly representative global digital network that its founders imagined the web to be.